Isolation and identification of chlorella-like species for potential application in biofuel production - Ismail, Nurfaiqah; Mohd Ashaari, Mardiana; Mohammad Noor, Normawaty; Abdul Halim, Khairul Bariyyah (2017)
In recent years, there has been an increasing interest in the study of microalgae for the development of biofuel, a renewable energy source. It is known that microalgae is able to accumulate lipid, thus hold great potential as biofuel feedstock. This project aimed to isolate and study Chlorella-like algae as a new biodiesel source. Water samples containing microalgae were obtained from the Fishery Research Institute, Tanjung Demong, Besut, Terengganu and freshwater lake, Kluang, Johor, Malaysia. Micractinium reisseri RAIW01 and Micractinium reisseri YSL006 were successfully isolated based on microscopic examination and LSU rDNA (D1-D2) sequence analysis. Studies on dry weight and lipid content of Micractinium reisseri RAIW01 showed this strain produce 0.117 ± 0.004 g dwt/ L and 0.028 ± 0.001 g/L respectively and major fatty acid composition was linolenic acid (37%). The biomass productivity, lipid cell content, and overall lipid productivity are some of the key parameters that determine the economic feasibility of algal oil for biodiesel production. Our results suggest that Micractinium reisseri RAIW01 can be a good candidate for biodiesel if lipid composition modification is carried out.